Penelusuran Bahan Pustaka online Melalui Internet di Perpustakaan Jurusan Biologi FMPA UNM - Andi Faridah, A research report of the composition of (Fakultas MIPA UNM, 2011)
Text book owned by the Biological Library of FMIPA UNM able to fulfill 70% requirement of student literature and 100% requirement teach by the teacher. Along with science progress in biological area, text book owned by the library require to be improved. But addition sum up the book did not correct solution because the addition sum up the book need the broader place, more amount time, and larger ones energy to manage the books. Biological Library of FMIPA UNM have the additional service that is service free acces internet. To assist the student to search of online study literature, researcher conduct the mentoring toward library visitor (student). This mentoring will know: